2006
DOI: 10.1029/2006gl026170
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of early spring temperature for central Japan from the tree‐ring widths of Hinoki cypress and its verification by other proxy records

Abstract: We describe the results of a dendroclimatic study in central Japan using ring width data from living trees of Hinoki cypress. February–April temperatures were reconstructed for the period AD 1719–1961. This reconstruction, from which five cooling events were determined for the late Little Ice Age, was validated against other climate proxies. There is a reasonable agreement with cold periods previously estimated from documentary records in Japan and China. A notably good agreement is also found for a dendroclim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 20 publications
3
48
0
Order By: Relevance
“…This study confirmed once again that winter-spring temperatures are the critical driving factor of tree radial growth (Fig.3); similar growth response relationships have been reported for Korean pine (Pinus koraiensis) in northeastern China (Zhu et al 2009), Hinoki cypress (Chamaecyparis obtusa) in central Japan (Yonenobu and Eckstein 2006), pine trees (Pinus massoniana) in southeastern China (Duan et al 2011), and Shensi fir (Abies chensiensis) in central China (Chen et al 2015). The above phenomenon may be caused by the photosynthetic Bmechanism^that is controlled by the temperature regime, and a higher winter-spring temperature prolongs the period of growth during which the trees are capable of photosynthesis.…”
Section: Discussionsupporting
confidence: 72%
“…This study confirmed once again that winter-spring temperatures are the critical driving factor of tree radial growth (Fig.3); similar growth response relationships have been reported for Korean pine (Pinus koraiensis) in northeastern China (Zhu et al 2009), Hinoki cypress (Chamaecyparis obtusa) in central Japan (Yonenobu and Eckstein 2006), pine trees (Pinus massoniana) in southeastern China (Duan et al 2011), and Shensi fir (Abies chensiensis) in central China (Chen et al 2015). The above phenomenon may be caused by the photosynthetic Bmechanism^that is controlled by the temperature regime, and a higher winter-spring temperature prolongs the period of growth during which the trees are capable of photosynthesis.…”
Section: Discussionsupporting
confidence: 72%
“…3) suggest that the radial growth of Korean Pine in Changbai Mountain is mainly limited by the pre-growth season temperature. A positive effect of winter temperature on tree growth was also reported for other temperate coniferous forests, such as in central Japan and in the Hudson River Valley (Pederson et al, 2004;Yonenobu and Eckstein, 2006), and from timberline forests on the east and northeast Tibetan Plateau (Brauning, 2001;Liang et al, 2009;Liu et al, 2007;Zhu et al, 2008). Warm winters may lead to damage to the roots and positive carbon gains for conifer trees when their leaves are not frozen (Brauning, 2001;Chabot and Hicks, 1982;Havranek and Tranquillini, 1995;Pederson et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Map showing the tree-ring sites, meteorological station, and other locations mentioned in text. CJ: Feburary-April temperature (Yonenobu and Eckstein, 2006); EC: Winter-half year temperature (Ge et al, 2003). The grids for the EAWMI are marked by the solid bars in the panel upper left.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations